Enhancing Tourism Students’ Vocabulary Mastery through Online Blogging Integrated with Vocabulary Self-Collection Strategy - Namirah Nurul Ilmi Achmad; Sari Hidayati (MASI Mandiri Edukasi, 2025)
This study addresses the limited vocabulary mastery among eleventh-grade tourism majors at SMKN 4 Yogyakarta, which hinders their ability to meet industry-specific communication demands. It aims to improve students’ vocabulary mastery by integrating the Vocabulary Self-Collection Strategy (VSS) with Blogger.com. This integration aligns with global educational trends emphasizing ICT integration and the development of vocational competencies. Blogger.com was a digital platform to enhance student engagement, promote independent learning, and support reflective vocabulary practice. Utilizing a Classroom Action Research (CAR) design, the study was implemented in two cycles involving 35 students. Data were collected through pre-tests, post-tests, interviews, and classroom observations. The findings showed a significant improvement in vocabulary mastery, with average scores rising from 60.88 (pre-test) to 91.88 (post-test in Cycle 2). Students also demonstrated increased motivation and engagement, supported by Blogger.com's interactive features and peer feedback mechanisms. Nevertheless, initial technical difficulties and challenges with phrasal verbs were identified. This study underscores the global relevance of integrating ICT tools like Blogger.com in vocational education to enrich vocabulary learning outcomes and recommends further technical training to optimize implementation.